THE EFFECT OF MOTIVATIONAL MEDIATION ON THE INFLUENCE OF LEARNING ORGANIZATIONS ON EMPLOYEE PERFORMANCE IN THE VUCA ERA - Hakim, Alif Lukmanul; Kapisa, Redi Yana; Supriatna, Metha Djuwita; Efendi, Bahtiar (ITB AAS Indonesia Surakarta, 2024)
This research is motivated by the importance of improving employee performance. This research aims to determine and analyze the mediating effect of motivation on the influence of learning organizations on employee performance in the VUCA era. This research method is a descriptive research method with a quantitative approach. The population in this study were employees of state-owned banks in Indonesia. The sample in this research was 100 employees with purpose sampling. The data collection technique is by distributing questionnaires using Google Form. The instruments used have been tested for validity and reliability. The collected data was analyzed using the classic assumption test and path test to see the influence and the Sobel test to see which variables were successful as mediators. The results of this research show that 1) Learning organizations influence Employee Performance in the Vuca Era and 2) Motivation mediates the influence of learning organizations on Employee Performance in the Vuca Era. The results of this research indicate that if companies want to improve employee performance, they must also improve organizational learning and employee motivation.